Post-peak Evolution of the Muskoka Domain, Western Grenville Province: Ductile Detachment Zone in a Crustalscale Metamorphic Core Complex - Rivers, Toby; Schwerdtner, Walfried (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2015)
The Ottawa River Gneiss Complex (ORGC) in the western Grenville Province of Ontario and Quebec is interpreted as the exhumed mid-crustal core of a large metamorphic core complex. This paper concerns the post-peak evolution of the Muskoka domain, the highest structural level in the southern ORGC that is largely composed of amphibolite-facies straight gneiss derived from retrogressed granulite-facies precursors. It is argued that retrogression and high strain occurred during orogenic collapse and that the Muskoka domain acted as the ductile detachment zone between two stronger crustal units, the underlying granulite-facies core known as the Algonquin domain and the overlying lower grade cover comprising the Composite Arc Belt. Formation of the metamorphic core complex followed Ottawan crustal thickening, peak metamorphism and possible channel flow, and took place in a regime of crustal thinning and gravitational collapse in which the cool brittle–ductile upper crust underwent megaboudinage and the underlying hot ductile mid crust flowed into the intervening megaboudin neck regions. Post-peak crustal thinning in the Muskoka domain began under suprasolidus conditions, was facilitated by widespread retrogression, and was heterogeneous, perhaps attaining ~90% locally. It was associated with a range of ductile, high-temperature extensional structures including multi-order boudinage and associated extensional bending folds, and a regional system of extension-dominated transtensional cross-folds. These ductile structures were followed by brittle–ductile fault propagation folding at higher crustal level after the gneiss complex was substantially exhumed and cooled. Collectively the data record ~60 m.y. of post-peak extension on the margin of an exceptionally large metamorphic core complex in which the ductile detachment zone has a true thickness of ~7 km. The large scale of the core complex is consistent with the deep level of erosion, and the long duration of extensional collapse is compatible with double thickness crust at the metamorphic peak, the presence of abundant leucosome in the mid crust and widespread fluidfluxed retrogression, collectively pointing to the important role of core complexes in crustal cooling after the peak of the Grenvillian Orogeny.